Solid organ transplantation programs facing lack of empiric evidence in the COVID‐19 pandemic: A By‐proxy Society Recommendation Consensus approach. Issue 7 (10th May 2020) - Ritschl, Paul V.; Nevermann, Nora; Wiering, Leke; Wu, Helen H.; Moroder, Philipp; Brandl, Andreas; Hillebrandt, Karl; Tacke, Frank; Friedersdorff, Frank; Schlomm, Thorsten; Schöning, Wenzel; Öllinger, Robert; et al.
Abstract : The ongoing severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic has a drastic impact on national health care systems. Given the overwhelming demand on facility capacity, the impact on all health care sectors has to be addressed. Solid organ transplantation represents a field with a high demand on staff, intensive care units, and follow‐up facilities. The great therapeutic value of organ transplantation has to be weighed against mandatory constraints of health care capacities. In addition, the management of immunosuppressed recipients has to be reassessed during the ongoing coronavirus disease 2019 (COVID‐19) pandemic. In addressing these crucial questions, transplant physicians are facing a total lack of scientific evidence. Therefore, the aim of this study was to offer an approach of consensus‐based guidance, derived from individual information of 22 transplant societies. Key recommendations were extracted and the degree of consensus among different organizations was calculated. A high degree of consensus was found for temporarily suspending nonurgent transplant procedures and living donation programs. Systematic polymerase chain reaction‐based testing of donors and recipients was broadly recommended. Additionally, more specific aspects (eg, screening of surgical explant teams and restricted use of marginal donor organs) were included in our analysis. This study offers a novel approach to informed guidance for health care management when a priori no scientific evidence is available. Abstract : This study summarizes recommendations of international societies on the management of transplant patients during the SARS‐CoV‐2 pandemic.